Simulation Analysis of the Sound Transmission Loss of Composite Laminated Cylindrical Shells with Applied Acoustic Coverings - Bin Li; Haoyang Ding; Zhigang Hu; Junya Zhao; Menghui Qi; Zhiyong Wang (Shock and Vibration)
The noise reduction problem of composite laminated cylindrical shells at low and medium frequencies from 150 Hz to 1000 Hz is addressed by using the noise control method of laying acoustic coverings and conducting noise reduction experiments in a cylindrical shell cavity by laying melamine foam, sound-absorbing cotton, and multilayer combination materials and obtaining the corresponding transmission loss curves. Additionally, based on the LMS Virtual Lab acoustic simulation software, finite element models corresponding to the noise reduction experiments are established, and the acoustic cavity’s simple positive frequency and acoustic response of the cavity are numerically calculated. Based on this, the influence law for a laid acoustic cover layer on the sound transmission loss of a cylindrical shell is investigated. The results show that the noise reduction of sound-absorbing cotton with the same thickness is about 1.26 times that of melamine foam, and the noise reduction of melamine foam with the same mass is about 1.42 times that of sound-absorbing cotton. For multilayer laying, the noise reduction of adding the same thickness of butyl rubber is about 6.18 times that of melamine foam, and the larger the laying ratio is, the better the noise reduction effect will be.